Investigating the Impact of Public Service Advertising on Blood Donation Intentions Under the Influence of Covid-19 Related Moderators - Mehmet Safa Çam (İletişim Kuram ve Araştırma Dergisi)
The objective of this research was to explore the role of Public Service Ads (PSAs) on blood donation decisions and the COVID-19 related mechanisms influencing the path to donation behavior. Although blood donation is shown as a form of behavior that is strongly motivated by emotional responses and altruistic behaviors, there are uncertainties in terms of difficulties that the donors experience during the pandemic period. A sample group consisting mostly of young people (N=189), received a self-administered questionnaire containing questions intended to clarify blood donation drives following exposure to a PSA stimulus. These factors comprised of the components for identification towards PSA characters, empathy, altruistic feelings towards blood donation behavior and donation intentions, and also pandemic related determinants. Regression-based analyzes were used to test the hypotheses, and the effects of COVID-19-derived factors on the blood donation process were investigated through moderator analysis. The results revealed that the empathy and identification levels towards PSA characters vary due to presenting whether the donor-type or the patient-type. No statistically significant results were found between the interactions of the risk of getting infected and altruistic feelings on blood donation intentions. However, it is concluded that pandemic fatigue significantly predicted the relationships between empathetic responses and altruistic feelings.